2018
DOI: 10.1002/jnr.24265
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clinical features of social cognition in 22q11.2 deletion syndrome

Abstract: 22q11.2 deletion syndrome (22q11.2 DS) is widely known as one of the most compelling genetic models of schizophrenia so far, being almost 40% of the carriers affected by psychotic symptoms. Moreover, most of these subjects also show impairment in social cognition, which is a comprehensive array of function that guides social interaction with the others, leading as well to the acquisition of new cognitive and social skills. In the last decade researchers have argued whether social cognition dysfunctions could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 122 publications
(140 reference statements)
2
11
0
5
Order By: Relevance
“…Finally, several studies reported associations between genetics and SC also in subjects with the 22q11.2 Deletion Syndrome (22q11.2 DS) that has a robust representation of genetic proneness to SSD (156)(157)(158)(159)(160)(161). There is a strong agreement in all the results reported showing that compared to healthy controls, 22q11.2 CNV subjects showed significantly poorer SC such as emotion differentiation, emotion recognition, lie detection, sarcasm detection.…”
Section: Molecular Biomarkers Of Social Cognitionmentioning
confidence: 83%
“…Finally, several studies reported associations between genetics and SC also in subjects with the 22q11.2 Deletion Syndrome (22q11.2 DS) that has a robust representation of genetic proneness to SSD (156)(157)(158)(159)(160)(161). There is a strong agreement in all the results reported showing that compared to healthy controls, 22q11.2 CNV subjects showed significantly poorer SC such as emotion differentiation, emotion recognition, lie detection, sarcasm detection.…”
Section: Molecular Biomarkers Of Social Cognitionmentioning
confidence: 83%
“…Daar is die afgelope tyd 'n hernude belangstelling in die genetika van skisofrenie en die funksionele inkortings wat daarmee saamhang, insluitend die kognitiewe inkortings wat sosiale kognisie onderlê. In 'n oorsig van die genetiese en kliniese kenmerke van sosiale kognisie by 22q11.2-mikroweglatingsindroom, beklemtoon Lattanzi et al (2018) 'n groep kandidaatgene wat veral van belang sou wees in 'n subgebied van 22q11.2. In volgorde van toenemende belang, bespreek die navorsers die volgende gene: ZDHHC8, RTN4R, DGCR8, PRODH en KOMT.…”
Section: Besprekingunclassified
“…Een van hierdie groepe word genoem 'Teorie van Verstand' en verwys na die vermoë om te verstaan wat in ander mense se gedagtes aangaan, en 'n idee te vorm van hulle emosies en geloofsoortuigings (Frith 1992). Tesame vorm kenmerke ten opsigte van die groepe verstandelike verwerkings die kognitiewe en gedragsfenotipe van skisofreniepasiënte se sosiale kognisie (Lattanzi et al 2018).…”
Section: Besprekingunclassified